PENGARUH KEMANFAATAN DAN KEMUDAHAN TERHADAP NIAT MENGGUNAKAN APLIKASI SIMANTAP P2S3 DENGAN TINGKAT PENDIDIKAN SEBAGAI VARIABEL MODERATOR - Su'ud Wahedi; Hali Makki (Al-Idarah, 2023)
SIMANTAP P2S3 is internet-based application that developed by Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo to fulfill students’ financial obligation. This paper aims to investigate relation usefulness, easyness, and intention of using SIMANTAP P2S3. However, education level is also used as moderated variable. There are 45 samples in this research. Moderated Regression Analysis is used to analayze data. This paper finds that usefulness and easiness influnce intention of using SIMANTAP P2S3. Nevertheless, education level does not moderate the influnce usefulness and easiness to intention of using SIMANTAP P2S3. However, sample size in this research is low. Suggested to next researchers to increase sample size in order to get more robust result.